La emisora escolar: estrategia didáctica para desarrollar competencias comunicativas de lectura y escritura en estudiantes de básica primaria - Nieto Duarte, Helman Yesid (Universidad Antonio Nariño, 2023)
The present investigation, developed in the Master's Degree in Education of the University Antonio Nariño, in Bogotá (Col.) sought to develop a strategy that mediated the development of the communicative competences of reading and writing in the students of the Female Lyceum Mercedes Nariño IED, official institution of the city.